Ancient sedimentary plant DNA dataset from Batagay (B17), Yakutia - Courtin, Jérémy (Zenodo, 2022)
Here we provide a dataset on genetic plant diversity retrieved from permafrost sedimentary ancient DNA (sedaDNA) of the Batagay megaslump, Yakutia. Our dataset encompasses sedaDNA sequence data of 10 sediment samples. We used a PCR-based metabarcoding approach combined with Next-Generation Sequencing to assess the past, local vegetation compositional changes around the megaslump. As a plant specific metabarcode we applied the established chloroplastidal P6 loop trnL marker for plant diversity assessment. PCR products were sequenced on one Illumina sequencing HiSeq 2500 run. For reanalysis of data we provide the following data files: 1. Illumina sequencing raw data of the sequencing run: ALRK-4. Data files are compressed. ALRK-4 (190315_NB501473_A_L1-4_ALRK-4_R1.fastq, 190315_NB501473_A_L1-4_ALRK-4_R2.fastq). 2. Two scripts to run the OBITools pipeline with a short description of each step. Data analyses with OBITools (Script_data_analyses_with_OBITools.txt) Database creation with EcoPCR and OBITools (Script_Database_creation_for_OBITools.txt) 3. Tagfiles needed for the OBITools pipeline with a corresponding file to associate the sample names in the tagfiles which indicate the sample batch number and corresponding controls (DNA extraction blank (BLANK) and PCR negative control (NTC)). ALRK-4: ALRK-4_tagfile.txt ALRK-4_names.txt 4. Taxonomic database files needed for the OBITools pipeline (see Script_data_analyses_with_OBITools.txt) EMBL database (g_h_embl138_final.uniqIDs.fasta) Arctic database (arctborbryo_gh.fasta, ecochange.zip) 5. Final data tables after bioinformatic analyses with OBITools. We provide the table with best taxonomic assignment. We the final name, we used the best name given by the database with the best identity score. If both databases were giving similar identity score, then we prioritise the arctic database. ALRK-4 (ALRK-4_final_assignment.txt) Funding provided by: European Research Council (ERC) under the European Union's Horizon 2020 research and innovation program* Crossref Funder ...